1982
DOI: 10.1104/pp.69.2.546
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Centrifugal Force and Centrifugation Time on the Sedimentation of Plant Organelles

Abstract: The effect of centrifugal force and length of centrifugation time on the sedimentation of plant organelles was determined for corn (Zea mays L.) root homogenates. A centrifugal force of 6000g for at least 20 minutes was necessary to pellet 90% of the mitochondrial marker (cytochrome c oxidase). This initial centrifugation step is optimal for separating mitochondria from microsomes, since cross-contamination of endoplasmic reticulum and plasma membrane vesicles with mitochondria is minimized. Centrifugal forces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…They reported that 93% of the mitochondria (Cyt c oxidase) were pelleted under these conditions, together with 35% of the PM (pH 6.5 K+-stimulated ATPase) and 28% of the ER (Antimycin A-insensitive NADH-Cyt c reductase). Under the same conditions (Table I), we pelleted 92% of the mitochondria, in agreement with Nagahashi and Hiraike (30), but substantially more PM (67% UDPG-ST), ER (37%) NADPH-Cyt c reductase), and Golgi (53% latent UDPase) were also removed. These differences could be due to several factors.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…They reported that 93% of the mitochondria (Cyt c oxidase) were pelleted under these conditions, together with 35% of the PM (pH 6.5 K+-stimulated ATPase) and 28% of the ER (Antimycin A-insensitive NADH-Cyt c reductase). Under the same conditions (Table I), we pelleted 92% of the mitochondria, in agreement with Nagahashi and Hiraike (30), but substantially more PM (67% UDPG-ST), ER (37%) NADPH-Cyt c reductase), and Golgi (53% latent UDPase) were also removed. These differences could be due to several factors.…”
supporting
confidence: 62%
“…The pH 7.5 KCl, Mg2+-ATPase again had a distribution similar to the Golgi marker, latent UDPase. (30) showed that an optimal separation of mitochondria and microsomes in corn roots could be achieved by an initial centrifugation of 6000g for 20 min. They reported that 93% of the mitochondria (Cyt c oxidase) were pelleted under these conditions, together with 35% of the PM (pH 6.5 K+-stimulated ATPase) and 28% of the ER (Antimycin A-insensitive NADH-Cyt c reductase).…”
mentioning
confidence: 99%
“…Similar analyses using either wild-type or crt1-2 crh1-1 plants containing an RPM1-Myc transgene revealed that RPM1-Myc also was predominantly located in the endomembranes, regardless of mock or Pst inoculation ( Figure 7B). Two-step differential centrifugation at 13,000 and 100,000g was then performed to fractionate organelles/vesicles based on size and density (Nagahashi and Hiraike, 1982). Consistent with the heterogeneous size of vesicles carrying CRT1, Myc-CRT1 was enriched in both the 13,000g (p13) and the 100,000g (p100) pellet fractions ( Figure 7C).…”
Section: Crt1 Is Localized In Endosomes Displaying Rapid Cytosolic Stmentioning
confidence: 70%
“…Pellets from subsequent, faster centrifugation steps were difficult to resuspend if the 1,lOOg centrifugation step was omitted. The crude homogenate was subjected to the differential centrifugation scheme of Nagahashi and Hiraike (20 …”
Section: Materials and Methods Preparation Of Crude Homogenates And Mmentioning
confidence: 99%